Sleep problems in children with autism spectrum disorder in Hong Kong: a cross-sectional study - Leung, Man Ho Brian; Ngan, Sze Ting Joanna; Cheng, Pak Wing Calvin; Chan, Fong Chun Grace; Chang, Wing Chung; Cheung, Hoi Kei; Ho, Chung; Lee, Chi Kei Krystal; Tang, Yiu Chung Vincent; Wong, Siu Man Corine; Chan, Kwok Ling Phyllis (Frontiers in Psychiatry, 2023)
Background: Autism spectrum disorder (ASD) is a neurodevelopmental disorder with growing prevalence of sleep problems, associated with significant behavioral problems and more severe autism clinical presentation. Little is known about the relationships between autism traits and sleep problems in Hong Kong. Therefore, the aim of this study is to examine whether children with autism have increased sleep problems than non-autistic children in Hong Kong. The secondary objective is to examine factors associated with sleep problems in an autism clinical sample. Method: This cross-sectional study recruited 135 children with autism and 102 with the same age range non-autistic children, aged 6-12. Both groups were screened and compared on their sleep behaviors using the Children’s Sleep Habits Questionnaire (CSHQ). Results: Children with autism had significantly more sleep problems than non-autistic children (t(226.73)= 6.20, p < .001). Bed-sharing (beta = 0.25, t(165) = 2.75, p = 0.07) and maternal age at birth (beta = 0.15, t(165) = 2.05, p = 0.043) were significant factors associated with CSHQ score on top of autism traits. Stepwise linear regression modelling identified that only separation anxiety disorder (beta = 4.83, t = 2.40, p =0.019) best predicted CSHQ. Conclusions: In summary, autistic children suffered from significantly more sleep problems and, co-occurring separation anxiety disorder bring greater sleep problems as compared to non-autistic children. Clinicians should be more aware of the sleep problems to provide more effective treatments to children with autism.